KELAYAKAN EKONOMI USAHATANI PORANG (Amorphophallus oncophyllus) DI KABUPATEN SINJAI - Sultan Sultan; Iskandar Hasan; Annas Boceng (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2022)
This study aims to: (1) describe the production process of porang farming in Pasir Putih Village, Sinjai Borong District, Sinjai Regency. (2) Analyzing the economic feasibility (income, R/C-Racio, BEP volume & BEP production value) of porang farming in Pasir Putih Village, Sinjai Borong District, Sinjai Regency. The choice of research location was determined intentionally (purposive sampling) with the consideration that the area is one of the centers of porang development in Sinjai Regency. Determination of the sample using the probability sampling method. Probability sampling was used for sampling farmers in three neighborhoods and the Slovin formula approach method was used to determine the number of respondents, namely 42 respondents. The results showed that: (1) the production process of porang farming in Pasir Putih Village, Sinjai Borong District, Sinjai Regency, namely land area, capital for the cost of seeds/seeds, pesticides and labor are also affected because the porang cultivation technique is still not optimal (not yet intensive). (2) The economic feasibility of porang farming in Pasir Putih Village, Sinjai Borong District, Sinjai Regency is known that the income of porang farming each respondent (0.78 Ha) is Rp. Rp. 26,134,822, - each hectare of Rp. Rp.34,313,535, - and the average total cost per respondent is Rp. 8,470,088,- or the total cost per hectare is Rp. 11.120,744. So that the income of porang farming per respondent each planting season is known to be Rp. 17,664,734 (for 6 months) or Rp. 2,944,122 /month. While the average income of porang each hectare each planting season is Rp. 23,192,791 (for 6 months) or Rp. 3,865,465/month. In porang farming, the R/C-Ratio value is 3.09. Based on the feasibility criteria of porang farming with the calculation of R/C-Ratio > 1, then porang farming is feasible to be developed. This means that for every porang farming expenditure of Rp. 1, the respondent will receive an income of Rp. 3.09. While the value of the break-even point (BEP) of production and price is smaller than the production and selling price of porang so that porang farming in Pasir Putih Village, Sinjai Borong District, Sinjai Regency is said to be profitable to cultivate